2021
DOI: 10.1186/s12891-021-04743-2
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of osteoporosis Care Organized by Nurses: ICON study - Protocol of a quasi-experimental study to assess the (cost)-effectiveness of combining a decision aid with motivational interviewing for improving medication persistence in patients with a recent fracture being treated at the fracture liaison service

Abstract: Background Given the health and economic burden of fractures related to osteoporosis, suboptimal adherence to medication and the increasing importance of shared-decision making, the Improvement of osteoporosis Care Organized by Nurses (ICON) study was designed to evaluate the effectiveness, cost-effectiveness and feasibility of a multi-component adherence intervention (MCAI) for patients with an indication for treatment with anti–osteoporosis medication, following assessment at the Fracture Lia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“…For this study, patients from the usual care group of the ICON study were included. All patients attended one of two FLS centers for fracture risk evaluation [ 9 ] (Maastricht University Medical Center (MUMC +) and VieCuri Medical Center Venlo, the Netherlands). The ICON study was approved by the Medical Ethics Committee of MUMC + /Maastricht University (UM), the Netherlands, registration number 2018–0575, and the trial was registered in the Netherlands Trial Registry (Trial NL7236 (NTR7435) Version 1.0; 26–11-2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, patients from the usual care group of the ICON study were included. All patients attended one of two FLS centers for fracture risk evaluation [ 9 ] (Maastricht University Medical Center (MUMC +) and VieCuri Medical Center Venlo, the Netherlands). The ICON study was approved by the Medical Ethics Committee of MUMC + /Maastricht University (UM), the Netherlands, registration number 2018–0575, and the trial was registered in the Netherlands Trial Registry (Trial NL7236 (NTR7435) Version 1.0; 26–11-2020).…”
Section: Methodsmentioning
confidence: 99%
“…The Improvement of osteoporosis Care Organized by Nurses (ICON) study offers an opportunity to address the above-mentioned gaps in knowledge by collecting real-world longitudinal data on patients visiting the FLS after a recent fracture and eligible for anti-osteoporosis medication (AOM) [ 9 ]. The ICON study (trial registration number 2018–0575) was developed to test the effect of a multi-component adherence intervention (MCAI) combining a patient decision aid [ 10 ] with motivational interviewing on medication persistence compared to usual care in patients attending an FLS after a recent fracture and collected societal costs before and up to 1 year after the first FLS visit.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the RDCI is more feasible to obtain and a more versatile index, performing well in both self-reported and administrative data (1,2). Because of its performance, feasibility, and versatility, it has been broadly used in RA studies (3) as well as in studies of psoriatic arthritis (4,5), spondyloarthritis (5)(6)(7), gout (8,9), lupus (10), vasculitis (11,12), and osteoporosis (13).…”
Section: Introductionmentioning
confidence: 99%
“…Middlebrook et al [ 12 ] delved further into improving musculoskeletal trauma recovery outcomes by evaluating patients' and physiotherapists' successful recovery perceptions to ensure alignment. Salmasi et al [ 13 ] reported on researchers' perspectives in an OMERACT adherence study, while Cornelissen et al [ 14 ] shared a co-designed multi-component adherence protocol for osteoporosis care.…”
Section: Introductionmentioning
confidence: 99%